2003
DOI: 10.1104/pp.103.026195
|View full text |Cite
|
Sign up to set email alerts
|

A Semidwarf Phenotype of Barley uzu Results from a Nucleotide Substitution in the Gene Encoding a Putative Brassinosteroid Receptor

Abstract: Brassinosteroids (BRs) play important roles throughout plant growth and development. Despite the importance of clarifying the mechanism of BR-related growth regulation in cereal crops, BR-related cereal mutants have been identified only in rice (Oryza sativa). We previously found that semidwarf barley (Hordeum vulgare) accessions carrying the "uzu" gene, called "uzu" barley in Japan, are non-responding for brassinolide (BL). We then performed chemical and molecular analyses to clarify the mechanisms of uzu dwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
202
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(216 citation statements)
references
References 72 publications
7
202
0
Order By: Relevance
“…Five of eight mutants induced in 'Steptoe' carried a 4-bp and a 1-bp deletion in the 39 untranslated region and two of four mutants induced in 'Akashinriki'-derived lines carried the same deletions plus three nucleotide substitutions that caused two nonsynonymous changes of amino acid residues (Ala-79 to Phe and Leu-1028 to Val) in the BRI1 N-and C-terminal domains, respectively (AkashinrikiII-allele; Chono et al, 2003). None of those haplotypes displayed an obvious brassinosteroid phenotype (Supplemental Data Set S1), which suggests that they are not deficient in HvBRI1.…”
Section: Genetic Characterization and Novel Alleles Of Hvbri1mentioning
confidence: 99%
“…Five of eight mutants induced in 'Steptoe' carried a 4-bp and a 1-bp deletion in the 39 untranslated region and two of four mutants induced in 'Akashinriki'-derived lines carried the same deletions plus three nucleotide substitutions that caused two nonsynonymous changes of amino acid residues (Ala-79 to Phe and Leu-1028 to Val) in the BRI1 N-and C-terminal domains, respectively (AkashinrikiII-allele; Chono et al, 2003). None of those haplotypes displayed an obvious brassinosteroid phenotype (Supplemental Data Set S1), which suggests that they are not deficient in HvBRI1.…”
Section: Genetic Characterization and Novel Alleles Of Hvbri1mentioning
confidence: 99%
“…Very recently, Chono et al 15) reported that a semi-dwarf gene in barley, uzu, encodes a putative BR receptor that is highly homologous to Arabidopsis AtBRI1 and rice OsBRI1. They found that this semi-dwarf barley cultivar, called uzu barley in Japanese, is less responsive to brassinolide and has a high accumulation of BRs.…”
Section: Dwarf Phenotype Of Rice Br-related Mutantsmentioning
confidence: 99%
“…To explore the feasibility of mutant gene identification using the SNP mapping data and synteny models, we analyzed five NILs where the identity of the mutant locus is known: BW069 and BW880 lines containing the THIRD OUTER GLUME (HvTRD1) gene on chromosome 1H (Whipple et al, 2010), BW898 containing HvVRS1 (Komatsuda et al, 2007) on 2H, BW885 containing HvUZU (Chono et al, 2003) on 3H, and two loci on chromosome 7H, namely BW638 containing the HvNUD1 gene (Taketa et al, 2008) and BW905 containing HvWAXY (Rohde et al, 1988). Based on the assumption that synteny is conserved with rice and that major structural rearrangements are absent, we estimated the number of genes contained within the introgressed segments.…”
Section: Exploiting Synteny For Gene Prediction In Barleymentioning
confidence: 99%
“…Barley mutants have been used to isolate or validate genes such as nitrate reductase (Somers et al, 1983), key genes in the anthocyanin pathway (von Wettstein, 2007), a gene responsible for the floral bract phenotype HOODED (Muller et al, 1995), the row-type gene SIX-ROWED SPIKE1 (VRS1; Komatsuda et al, 2007), the hull adhesion gene NAKED CARYOPSIS (NUD; Taketa et al, 2008), plant height genes UZU DWARF (UZU; Chono et al, 2003) and SLENDER1 (Chandler et al, 2002), several endosperm development genes (Felker et al, 1983;Morell et al, 2003;Rö der et al, 2006;Clarke et al, 2008), and two disease lesion mimic mutations NECROTIC1 (Rostoks et al, 2006) and NECROTIC.S1 (Zhang et al, 2009) among others. However, despite these individual achievements, with few exceptions (Pozzi et al, 2003;Rossini et al, 2006), the barley mutant resources have not yet been systematically explored using the tools of modern genetics.…”
mentioning
confidence: 99%